2018
DOI: 10.1371/journal.pone.0197572
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of a contraceptive vaginal ring in women at risk of HIV infection in Rwanda: Safety of intermittent and continuous use

Abstract: BackgroundContraceptive vaginal rings could play a role in expanding the contraceptive method mix and in preparing communities for the introduction of HIV prevention and multipurpose rings.MethodsWe conducted an open label single-centre randomised clinical trial of intermittent versus continuous use of NuvaRing® in Kigali, Rwanda, in 2013–2014. We randomised 120 HIV-negative women 1:1 to intermittent use (three rings with a ring-free week in between rings) or continuous use (four rings without ring-free weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…The CCVR group also had a higher number of Candida infections compared to the other groups. In Rwandan women, the percentage of women with vaginal yeast increased from 5 to 22% after CCVR initiation 46 , and in vitro data corroborate this 47 , further supporting this possibility. Many different vaginal rings are currently in clinical trials, and our findings may be specific to NuvaRing®.…”
Section: Discussionmentioning
confidence: 57%
“…The CCVR group also had a higher number of Candida infections compared to the other groups. In Rwandan women, the percentage of women with vaginal yeast increased from 5 to 22% after CCVR initiation 46 , and in vitro data corroborate this 47 , further supporting this possibility. Many different vaginal rings are currently in clinical trials, and our findings may be specific to NuvaRing®.…”
Section: Discussionmentioning
confidence: 57%
“…We undertook this pilot to determine whether hormonal contraception following antibiotic therapy reduced BV-recurrence compared to antibiotic therapy alone and to assess the feasibility of the intervention. Women using hormonal contraception have a reduction in BV in a number of observational studies 13,15 , and a recent NuvaRing® trial in 120 women showed improved mean Nugent scores over 3-months 16 . A favourable effect of combined oestrogen-progesterone contraception on the vaginal microbiota may be explained by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We screened 769 abstracts and 17 full-text reports (online supplementary figure 1). We excluded 13 full-text reports – four reported on data already included in the 2016 review, six were letters or conference abstracts, and three had an irrelevant exposure, outcome or comparison group 12–24. From a conference abstract,13 we identified an additional 'in press' study, which has now been published 25.…”
Section: Resultsmentioning
confidence: 99%